Electronic Music / [electronic resource] - Collins, Nick; Schedel, Margaret; Wilson, Scott (Cambridge : Cambridge University Press, 2013)
This accessible Introduction explores both mainstream and experimental manifestations of electronic music. From early recording equipment to the most recent multimedia performances, the history of electronic music is full of interesting characters, fascinating and unusual music, and radical technology. Covering many different eras, genres and media, analyses of works appear alongside critical discussion of central ideas and themes, making this an essential guide for anyone approaching the subject for the first time. Chapters include key topics from synth pop to sound art, from electronic dance music to electrical instruments, and from the expression of pure sound to audiovisuals. Highly illustrated and with a wide selection of examples, the book provides many suggestions for further reading and listening to encourage students to begin their own experiments in this exciting field.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).